Two sulfur and nitrogen-rich cobalt–thiacalix[4]arene compounds for the selective mercury removal from aqueous solutions. Issue 44 (22nd October 2020) - Li, Kaiyue; Liao, Wuping
Abstract : Two thiacalix[4]arene-based coordination compounds, a Co 24 octahedral coordination cage and a Co 8 cluster, are effective adsorbents towards Hg(ii ) and the adsorption capacity of the Co 24 cage compound reaches 330 mg g −1 . Abstract : Due to the great harm to the environment and biology, the removal of mercury ions from wastewater is one of the most urgent tasks. Here, we designed and prepared two metal–calixarene coordination compounds, [Co4 (TC4A)(SO4 )]6 (L)6 (HCOO)6 12− (CIAC-131 ) and [Co4 (TC4A)2 ]2 L 3− (CIAC-251 ) (H4 TC4A = p-tert -butylthiacalix[4]arene, L = 1 H -1, 2, 3-triazole-4, 5-dicarboxylic acid) for the selective removal of mercury ions from aqueous solutions. Owing to their rich sulfur and nitrogen sites, both compounds exhibit high selectivity towards mercury ions and the adsorption capacity of CIAC-131 is higher than that of CIAC-251 . For CIAC-131, the adsorption capacity of Hg(ii ) is 330 mg g −1 and the removal efficiency of Hg(ii ) with an initial concentration at 50 mg L −1 in the aqueous solution is 98.8%. The gas sorption measurement was carried out to evaluate the porosity of CIAC-131 .